Tongues as of Fire: Pentecost as a Temple Inauguration Theophany - Griffiths, John D. (2023)
The coming of the Spirit of God at Pentecost (Acts 2.1-4) is described in dense imagery, involving auditory, visual, and somatic elements. This study outlines the recent scholarship on these theophanic elements, and in particular, the parallels with the temple inauguration theophanies in the Old Testament. While these parallels are increasingly becoming accepted, the implications of the temple inauguration imagery in Acts 2.1-4 remains unresolved. The core issue revolves around whether it is the Spirit or Jesus who now embodies the theophanic presence of God which once resided in the Jerusalem temple. This study concludes that it is the Spirit of God that now embodies the glory of God which resided in the temple, with the early Jesus community being the new eschatological temple of God.
Keywords: tongues of fire; temple inauguration; Theophany; Holy Spirit; Acts 2; Pentecost